2018
DOI: 10.1016/j.pneurobio.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing endogenous capacity to repair a stroke-damaged brain: An evolving field for stroke research

Abstract: Stroke represents a severe medical condition that causes stroke survivors to suffer from long-term and even lifelong disability. Over the past several decades, a vast majority of stroke research targets neuroprotection in the acute phase, while little work has been done to enhance stroke recovery at the later stage. Through reviewing current understanding of brain plasticity, stroke pathology, and emerging preclinical and clinical restorative approaches, this review aims to provide new insights to advance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 379 publications
(492 reference statements)
2
84
0
Order By: Relevance
“…We observed an increased number of BrdU-positive cells within the peri-infarct regions in stroke mice treated with GH, which is consistent with previous studies demonstrating that GH promotes cell proliferation within the central nervous system [52,53]. Critically, these progenitor cells are known to release neurotrophic factors to provide an environment which may contribute to neural network remodelling and functional recovery [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…We observed an increased number of BrdU-positive cells within the peri-infarct regions in stroke mice treated with GH, which is consistent with previous studies demonstrating that GH promotes cell proliferation within the central nervous system [52,53]. Critically, these progenitor cells are known to release neurotrophic factors to provide an environment which may contribute to neural network remodelling and functional recovery [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…According to the pivotal role of oxidative stress and neuroinflammation in cellular injury during cerebral ischaemia/reperfusion, antioxidant and anti‐inflammatory agents can serve as potential targets for the management of ischaemic stroke . In recent years, the neuroprotective activity of antioxidants in animal models of ischaemic stroke has been distinctly established .…”
Section: Introductionmentioning
confidence: 99%
“…[6] According to the pivotal role of oxidative stress and neuroinflammation in cellular injury during cerebral ischaemia/ reperfusion, antioxidant and anti-inflammatory agents can serve as potential targets for the management of ischaemic stroke. [7] In recent years, the neuroprotective activity of antioxidants in animal models of ischaemic stroke has been distinctly established. [8,9] Besides, clinical trials have shown that the administration of antioxidant agents improve the clinical outcomes in patients suffering from acute cerebrovascular ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…While p38 has already been proven as a therapeutic target for acute stroke intervention, it is unclear whether p38 also plays a critical role in impairing functional recovery during the subacute phase of stroke which embodies brain repair initiation [6][7][8]. Time course analyses of phospho-p38 (i.e.…”
Section: Pagementioning
confidence: 99%
“…Based on pathological characteristics and their timing, a stroke is classified into three clinical phases, including the acute (i.e. first 48 hours after stroke onset), the subacute (from 48 hours to >6 weeks post stroke) and the chronic phase (starts at 3-6 months post stroke) [6]. The acute phase represents an opportunity to salvage threatened tissue and reduce the extent of injury, for example via reperfusion or neuroprotection [7,8].…”
Section: Introductionmentioning
confidence: 99%